2021
DOI: 10.3389/fpsyg.2021.645246
|View full text |Cite
|
Sign up to set email alerts
|

Psychedelic Harm Reduction and Integration: A Transtheoretical Model for Clinical Practice

Abstract: Psychedelic Harm Reduction and Integration (PHRI) is a transtheoretical and transdiagnostic clinical approach to working with patients who are using or considering using psychedelics in any context. The ongoing discussion of psychedelics in academic research and mainstream media, coupled with recent law enforcement deprioritization of psychedelics and compassionate use approvals for psychedelic-assisted therapy, make this model exceedingly timely. Given the prevalence of psychedelic use, the therapeutic potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
80
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 124 publications
(97 reference statements)
1
80
0
1
Order By: Relevance
“…Psychedelics are not recommended as purely pharmacological interventions. However, integrated psychotherapeutic frameworks grounded in empirically supported processes throughout the three phases of psychedelic-assisted therapy, are only just beginning to emerge, and mainly focus on the preparation and integration phases (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Psychedelics are not recommended as purely pharmacological interventions. However, integrated psychotherapeutic frameworks grounded in empirically supported processes throughout the three phases of psychedelic-assisted therapy, are only just beginning to emerge, and mainly focus on the preparation and integration phases (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals who use psychedelics often cite curiosity, the desire to seek mystical experiences, and self-medication as reasons for use (Lerner & Lyvers, 2006;Móró et al, 2011) and have also been found to occasionally seek mental health services after particularly challenging experiences (Carbonaro et al, 2016;Davis et al, 2020). In these events, counselors may consider similar approaches as described in the previous paragraph on integration and may further explore aspects of what are known as "set" and "setting," which have significant influence on how psychedelics are experienced (Carhart-Harris et al, 2018;Gorman et al, 2021). Set refers to the clients' intentions, affect, and outlook shortly prior to and during the experience, whereas setting captures the physical context in which the experience occurred and people who may have been present for it.…”
Section: Ongoing Psychedelic Integrationmentioning
confidence: 99%
“…Still, counselors are likely to encounter cases in which established clients inquire about or are insistent upon personal use. Thus, counselors may adopt a risk-reduction perspective by accurately providing information about psychedelics, their effects, and common responses (Gorman et al, 2021) and discussing challenges of nonclinical use, such as difficulty in verifying identity or dose of the drug consumed. Risk reduction includes reviewing psychological and safety contraindications for psychedelic use (Gorman et al, 2021), including personal or close family history of psychosis, comorbid borderline personality disorder, current use of antidepressant drugs, and untreated hypertension (O'Donnell et al, 2019), and encouraging clients to also consult a physician prior to engaging in personal use.…”
Section: Ongoing Psychedelic Integrationmentioning
confidence: 99%
See 2 more Smart Citations